Supramolecular Chemistry 2012
DOI: 10.1002/9780470661345.smc008
|View full text |Cite
|
Sign up to set email alerts
|

Multivalency

Abstract: Multivalent interactions, in which multiple ligands on one entity bind simultaneously to multiple receptors on another, are ubiquitous in nature. The use of multivalent agents will undoubtedly transform existing methods that target important disease processes including infection, immune system regulation, cancer, and neurological pathways. The employment of multivalent systems as tools to study biological recognition processes and for therapeutic development is unique in that multivalency can address many prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 110 publications
0
10
0
Order By: Relevance
“…108 This concept is an example of the principle of multivalency in supramolecular chemistry. 109 Adsorption studies conducted by Lee and coworkers have 90 provided evidence for the superior performance of PVCap relative to PVP, by studying the adsorption on cyclopentane hydrates. 110 Calculation of the adsorption isotherms for both vinyl lactam polymers has concluded that PVP follows the Langmuir isotherm whilst PVCap follows the BET-type; the combination of 95 the increased molecular size and multilayer adsorption as seen for PVCap results in inhibition performance exceeding that for PVP.…”
Section: Macroscopic Studies Of Khismentioning
confidence: 99%
“…108 This concept is an example of the principle of multivalency in supramolecular chemistry. 109 Adsorption studies conducted by Lee and coworkers have 90 provided evidence for the superior performance of PVCap relative to PVP, by studying the adsorption on cyclopentane hydrates. 110 Calculation of the adsorption isotherms for both vinyl lactam polymers has concluded that PVP follows the Langmuir isotherm whilst PVCap follows the BET-type; the combination of 95 the increased molecular size and multilayer adsorption as seen for PVCap results in inhibition performance exceeding that for PVP.…”
Section: Macroscopic Studies Of Khismentioning
confidence: 99%
“…From the above discussion of galectin-1 mediated cellular mechanisms in cancer, it should be understood that galectin-1 interacts multivalently with glycosylated receptors throughout the metastatic progression of cancer. Because a single interaction between a carbohydrate and its receptor (e.g., protein) is attenuated [ 7 ], nature presents multiple copies of receptors to enhance individual binding interactions and to elicit a biological response [ 1 , 2 ]. To better understand multivalent protein–carbohydrate interactions in cancer, synthetic multivalent frameworks can be applied to modulate native multivalent cellular mechanisms [ 123 ].…”
Section: Synthetic Multivalent Systems For Binding Of Galectin-1mentioning
confidence: 99%
“…Multivalency, the binding of multiple ligands to multiple receptor binding sites [ 1 , 2 ], provides a platform to better understand cellular mechanisms that drive cancer metastasis. Multivalent protein–carbohydrate interactions mediate a myriad of malignant cellular processes, including cellular aggregation/tumor formation, metastasis, and angiogenesis [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multivalent drug-polymer conjugates, in which multiple copies of a drug are covalently attached to a polymeric scaffold either directly or through linker chemistry, are a highly studied pathway to improve therapeutic index. 1 7 In particular, conjugation of methotrexate (MTX) to poly(amidoamine) (PAMAM) dendrimer has been extensively studied, with over 100 related publications since 2002. 8 19 Acetylated, neutral G5 PAMAM has been of particular interest as a drug delivery vector because of its narrow polydispersity index (PDI), low toxicity and immunogenicity, and molecular weight (MW) of about 30 kDa that allows it to solubilize multiple hydrophobic ligands while still being small enough to diffuse through tissue for cell-level targeting.…”
Section: Introductionmentioning
confidence: 99%